A novel patient-derived cutaneous melanoma cell line reveals key features of metastatic melanoma - Tomás, Ana; Roque, Lúcia; Francisco, Inês; Silva, Ana Luísa; Nunes, Hugo; Gouveia, Emanuel; Carvalho, Elisabete; Farricha, Victor; Moura, Cecília; Rosa, Joaninha Costa; Garrido, Pedro Miguel; Albuquerque, Cristina; et al. (Frontiers in Oncology, 2025)
IntroductionCutaneous melanoma (CM) is an aggressive form of skin cancer, with rising incidence and poor prognosis at advanced stages. While early-stage CM typically carries a favorable prognosis, a small subset of patients relapses and progresses to advanced disease, highlighting the need for a deeper understanding of CM biology. Here, we describe the establishment and characterization of a novel patient-derived primary cell line, MelT79, developed from a metastatic lesion of a patient initially diagnosed with stage IB CM, who unexpectedly progressed to advanced disease.MethodsMelT79 was characterized by multicolor fluorescence in situ hybridization, high resolution comparative genomic hybridization, and targeted next-generation sequencing. Gene and protein expression were evaluated by RT-qPCR and immunofluorescence, and cell proliferation was assessed using trypan blue exclusion and BrdU incorporation assays. Sensitivity to BRAF inhibition was measured with the Cell Counting Kit-8 viability assay. Gene and protein expression, proliferation, and drug sensitivity were compared to commercially available CM cell lines.ResultsMelT79 exhibits a complex karyotype with significant chromosomal alterations, including deletions affecting key genes such as CDKN2A/B, SPRED1, and B2M, implicated in melanomagenesis and therapy resistance. Additionally, MelT79 harbors both the BRAF V600E mutation and a rare RET S649L mutation, which has not been previously reported in CM. RET S649L was also identified in an earlier metastatic lesion, possibly conferring a selective advantage, and highlighting this mutation as a potential therapeutic target. Phenotypically, MelT79 displays both differentiation and invasive traits, suggesting that its heterogeneity might contribute to progression and therapy resistance. Furthermore, the cell line exhibited moderate sensitivity to BRAF and MEK inhibitors when compared to other commercially available cell lines, reflecting its heterogeneity.ConclusionMelT79 represents a valuable model for understanding CM heterogeneity, progression, and resistance mechanisms, offering new avenues for novel therapeutic interventions in CM.